BUILDING COMMUNICATION BRIDGES BETWEEN SHORELINE ANGLERS AND NATURAL RESOURCE POLICYMAKERS - (:unkn) unknown (My University, 2024)
Fishing has been a vital aspect of Wisconsin’s rich cultural history, predating statehood, to the earliest indigenous communities. A deep fishing heritage continued to grow with the arrival of European settlers through the 19th and 20th centuries, and continues today where fishing provides a means of recreation, a source of sustenance, and supports a multibillion-dollar industry. Wisconsin’s fisheries offer diverse commercial, recreational, and tribal angling opportunities. This resource supports thousands of jobs and is a vital aspect to local, state, and national economies. Many large municipalities along the Great Lakes, such as Milwaukee, are built near estuaries and harbors which are highly modified aquatic habitats that provide shoreline angling opportunities. The combination of shoreline angling locations near urban areas attracts a community of shoreline anglers that represent diverse racial, socioeconomic, and educational backgrounds. However, lacking representation in policymaking forums, these communities’ angling interests and perspectives are often overlooked. This study provides a comprehensive literature review to evaluate the current state of knowledge on the history of shoreline angling in Milwaukee County, current barriers to fishing participation, and science and policy communication techniques. We conducted a quantitative survey of shoreline anglers throughout Milwaukee County to characterize various subgroups within the shoreline angling community, identify their preferences, motivations, and sources of information, and the preferred mechanisms to solicit input in policy processes from these stakeholders. We also conducted a policy analysis to determine if and how the diverse perspectives of shoreline anglers are incorporated into policy decisions. We surveyed Wisconsin Department of Natural Resources (hereafter: “DNR”) fisheries staff to understand their approaches to stakeholder engagement. Then we compared the published policy documents to survey results from the cohort of shoreline anglers and DNR staff. We found shoreline anglers in Milwaukee County represent a racially, socioeconomically, and educationally diverse community, with a variety of perspectives, motivations, and primary sources of information for fishing. We hypothesized that due to the lack of organizational representation in policymaking fora, shoreline anglers’ interests and perspectives were not adequately incorporated into fisheries policy decisions. From this study, we aim to characterize shoreline angling communities, their characteristics, perspectives, and interests in fisheries management, and to recommend effective policy communication best practices that will allow for more diverse, equitable, and inclusive policymaking processes. This study provides a case study and model for natural resource management agencies to better understand and incorporate racially, socioeconomically, and educationally diverse stakeholder groups into policy decisions.
Keywords: Fishing; Natural Resource; Policy; Science Communication; Shoreline; Water Policy